Efektivitas Kelompok Usaha Bersama di Desa Banglas Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - Silvia, Silvia; Sujianto, Sujianto (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: Empowerment of the poor carried out by the government is a joint business group (KUBE), which is a family group that is formed, grows and develops on its initiative in carrying out productive economic efforts to increase family income. Meanwhile, after the formation of the Joint Business Group (KUBE) in Banglas Village, there were problems in the implementation of activities that were not optimal, because not all members were involved in every KUBE activity, thus hampering business development. The purpose of this study was to find out how the effectiveness of the implementation of the Joint Business Group (KUBE) in Banglas Village and to find out the obstacles or obstacles. Research Methodology: To be able to answer these problems, the author used a qualitative research method with a descriptive approach. Results: The results of this study find that the effectiveness of the Joint Business Group (KUBE) in Banglas Village, Tebing Tinggi District, Meranti Islands Regency is still less effective and not optimal in its implementation because there are still inhibiting factors, namely conflicts between members which cause KUBE management to not function properly. Some issues such as lack skills and Human Resources (HR), and unfair competition are also found. Limitations: In this study, the authors lack clear information regarding the division of tasks and completeness of data or information regarding the KUBE organization. Contribution: Theoretically, this research serves as a medium of continuous comparison for future research on the same topic or problem. It can bring up problem-solving models or new ideas in the implementation of the KUBE organization to develop managed products to be more attractive and ogled by the market and better known by the wider community.